Energy Supply & Optimization of New Tannery in Bangladesh - Åkerling, Gabriel; Ekberg, Carl (Luleå tekniska universitet, Institutionen för teknikvetenskap och matematik, 2018)
Böle Garveri is a tannery located outside Piteå with a long history of leather production. They are planning a new tannery in Bangladesh as a step in their ongoing expansion of their business. The leather industry in Bangladesh is currently chemically heavy and in many cases highly toxic to the environment. Böle Garveri intends to change the view of the leather industry with their green tanning process and commissioned this project to energy map the tannery, optimize their production and investigate the possibilities of becoming self sustaining with power production. The investigated parts of the production was transport and cooling of hides, drying of the tanned leather and the supply of heat and electricity. The tannery will be situated in the Bagatipara region of Bangladesh, occupy an area of 1500 m2 and have an annual capacity of 20 tonnes finished leather. It will employ 42 people directly and up to 5000 farmers indirectly. As the hides are delivered raw, there is need for cooling both during transport and in the tanneries storage facility. The recommended transportation option is to use an insulated truck without active cooling. The recommended coldstorage solution is a cold room of 4,2x3,4 m, insulated with 200 mm polyurethane boards which results in a capacity of 103 hides. The room will be cooled with a compressor driven heat pump with an effect of 2 kW, operating with air on bothcondenser and evaporator side. The recommended dryer is a hot air dryer with a heat-exchanger between ingoing and outgoing air, which is heated by the outgoing stream from the power production. It has a capacity to dry 31 hides in 36 hours and has a required power of 4,1kw which yield a theoretical efficiency of 50 %. Results from the energy mapping shows that the tannery will need 190 MWh thermal energy and 62 MWh electrical energy annually. To cover this demand the recommendation is to invest in a 130 m3, plug-flow type digester operating with co-digestion of manure and bagasse. The annual substrate demand of the biogas plant ...